1913, Satyagraha, Passive Resistance and its Legacy - Govinden, Devarakshanam,; Hiralal, Kalpana, (Brill | Manohar Publishers & Distributors, 2015)
This book marks the centenary of the 1913 Satyagraha Passive Resistance movement in South Africa, with the various contributors critically examining the significance and relevance of satyagraha from different vantage points. Satyagraha, first coined, developed and practised in South Africa, continues to challenge and inspire individuals and peoples far and wide. With unrelenting conﬂicts across the world, leading to deaths, violence and displacements of families and communities, the need for social and political transformation and the moral quest for the harmony of all humanity is as pressing today as it ever was. The volume is significant as it forces us to not only deepen our critical understanding of the past, but also to know this past as the legacy from which we draw for the present and future. The essays here show that there has been a continual attempt to understand and grapple with the term 'Satyagraha'. Some have been at pains to remind adherents of the essence of Satyagraha. At the same time, there were those who modified and adapted Satyagraha according to their own understandings and objectives or who used the idea as a strategy rather than as an ideal. While some clung to the ideal of Satyagraha, others did not violate its principles through a lack of understanding, but felt that a purist interpretation was not feasible on the ground. The shifting and ﬂuid differences on a wide spectrum among many who worked with Gandhi or with his concept of Satyagraha are reﬂected in the essays in this collection.